Structures of Werner clathrates - Bond, Dianne Ruth (Department of Chemistry, 2023)
The structures of two new Werner clathrates have been elucidated by X-ray diffraction. Ni(NCS) 2(c6 Hf) 2(c11ttgN) 2.methyl cello solve is monoclinic with a= 10,648(5), b = 23,005(12), a= 16,294(8).R, S = 98,04(2) 0 , Z = 4 and the space group C2/0 • The guest, methyl cello solve is disordered and lies at a centre of inversion. Ni(NCS) 2(c6 H7 N) 4.p-cymene is tetragonal with a= 17,105(9), b = 17, 105(9), a= 23,837(12).R, Z = 8 and the space group I4 1 fa• The guest, p-cymene is disordered and lies at a centre of inversion. The stoichiometry of the clathrates was investigated by various chemical methods including thermogravimetric analysis, differential thermal analysis, mass spectroscopy and proton nuclear magnetic resonance spectroscopy. Host-guest non-bonded energy relationships using atom-pair potentials are examined. Attempts have been made to estimate the association constants of sore of these computed in solution by proton nuclear magnetic resonance spectroscopy.